Akad dalam Student Loan; Analisis Implementasi di BMT UMY - Raya, Fitri; Muhamad Turmudi; Eva Savanda (Institut Agama Islam Negeri Madura, 2025)
Abstract Education financing is one of the big challenges in the world of higher education, especially for students who need funds to continue their studies. One solution that is developing is a student loan program provided by sharia microfinance institutions, such as BMT UMY. This article aims to analyze the implementation of contracts in the education financing program provided by BMT UMY, with a focus on the suitability of the sharia principles applied. Through a qualitative approach, this research explores the types of contracts applied in education financing, such as murabahah, mudharabah, and musyarakah contracts, as well as how BMT UMY adapts these contracts to meet student needs ethically and transparently. This analysis also discusses the challenges and benefits faced by institutions, students and related parties in implementing this program. The research results show that BMT UMY has succeeded in integrating sharia principles in education financing, but still faces challenges in terms of product socialization and financing risk management. It is hoped that this article can contribute to the development of a comprehensive and sustainable sharia-based education financing model in the future